Efektivitas Membran Reverse Osmosis pada Pengolahan Limbah Cair di Industri Migas - Anggraini, Adinda Dhayu; Mulyanti, Heri (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2025)
This study aims to evaluate the effectiveness of Reverse Osmosis (RO) membranes in reducing Total Dissolved Solids (TDS) in wastewater treatment in the oil and gas industry. High levels of TDS in industrial wastewater can affect equipment performance and does not meet water quality standards. The study used a descriptive quantitative approach with observation, interviews, literature studies, and company data analysis methods. The RO system implemented included pretreatment, chemical injection, high-pressure filtration, and storage of treated water. The results showed a significant decrease in TDS from 1,200 mg/L to 150 mg/L (efficiency 87.5%), turbidity from 3.2 NTU to 0.8 NTU (75%), and total hardness from 450 mg/L to 80 mg/L (82.2%), while pH was stable in the range of 6.8–7.1. These results prove that RO technology is capable of producing water with quality that meets the quality standards of the Minister of Health Regulation No. 492 of 2010. This study confirms the superiority of RO as an effective industrial water treatment method and recommends further research on operational costs, energy efficiency, and fouling control for long-term optimization.